Diffusion-based tractography in neurological disorders: concepts, applications, and future developments. - Ciccarelli, O; Catani, M; Johansen-Berg, H; Clark, C; Thompson, A (2008)
Diffusion-based tractography enables the graphical reconstruction of the white matter pathways in the brain and spinal cord of living humans. This technique has many potential clinical applications, including the investigation of stroke, multiple sclerosis, epilepsy, neurodegenerative diseases, and spinal cord disorders, and it enables hypotheses to be tested that could not previously be considered in living humans. This Review will outline the limitations of tractography, describe its current clinical applications in the most common neurological diseases, and highlight future opportunities.